Phosphoric Acid: Purification. - Gilmour, Rodney (CRC Press, 2014)
The rise and rationalization of the industrial phosphates industry have gone hand in hand with the development and maturation of technologies to purify phosphoric acid. In the 1960s and 70s, driven by the exponential sales growth of the detergent-builder sodium tripolyphosphate, chemical producers raced to develop processes that would provide a sufficiently pure phosphoric acid feedstock for manufacture to undercut thermal phosphoric acid made from phosphorus. As environmental and political pressure led to a collapse in demand for sodium tripolyphosphate in the 1990s, the commercial pressur.